MODEL STUDENT TEAM ACHIEVEMENT DIVISIONS BERBANTU MEDIA POP UP BOOK DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Alifiani Masithohsari; Fina Fakhriyah; Sekar Dwi Ardianti (Universitas Muhammadiyah Makassar, 2020)
This study aims to improve students' critical thinking skills through the STAD learning model aided by the Cita-Citaku 6 Theme Pop Up Book. This type of research is Classroom Action Research (CAR) which consists of the planning stage, the action stage, the observation stage and the reflection phase. The subjects in this study were students in grade IV SDN Margorejo 01 in the 2019/2020 Academic Year, totaling 22 students. Methods of data collection through test and non-test techniques. Analysis of the data used in this study is the analysis of qualitative and quantitative data. The results showed that the critical thinking ability of students in the first cycle was 72% and the second cycle increased to 80%. Student learning activities aspects of attitude in the first cycle by 73% and the second cycle increased to 82%. Meanwhile, the learning activities of students in the aspect of skills in the first cycle by 74% and the second cycle increased to 84%. Based on the results of the study it can be concluded that the STAD learning model helped by Pop Up Book media can improve the critical thinking skills of fourth grade students at SDN Margorejo 01.